CERTYFIKACJA ZNAJOMOŚCI JĘZYKÓW OBCYCH DLA CELÓW SPECJALISTYCZNYCH – MIĘDZY TEORIĄ A RZECZYWISTOŚCIĄ - Sendur, Agnieszka M. (Neofilolog, 2020)
A certificate proving the holder’s proficiency in a foreign language for specific purposes (LSP) should guarantee that the person submitting such a document is able to perform specific professional tasks using the particular foreign language. Therefore, an examination measuring such competencies should meet certain requirements and have certain characteristics. What are the differences between testing languages for general and for specific purposes? Are these differences visible in existing certificate examinations? Do the language certificates issued on the basis of LSP examinations give employers a guarantee that the employee can handle professional tasks which demand the use of the foreign language in question? In an attempt to answer these queries, the article will outline the theoretical principles behind testing languages for specific purposes and try to compare the theory and practice through an analysis of several LSP exams available on the market. Reflecting on the observations, it will also try to determine why the reality is often so distant from the theoretical foundations.